The Development of Cultural Attraction Routes in Sing Buri Province: การพัฒนาเส้นทางท่องเที่ยวมรดกวัฒนธรรมจังหวัดสิงห์บุรี - สวณภักดี ชนินทร (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
The purposes of this research were to: 1) Explore the cultural heritage resources of Sing Buri and 2) Initiate the cultural attraction routes development in Sing Buri province. Using the concept of community tourism as the basis for the creation of tourist routes, and the qualitative research methods including documentary research, survey, field observation, and interview; the data were collected to study the potential of tourist destinations. The topics of study are: heritage sites, conservation and maintenance, tourism management, facilitation, learning sources and tourist attraction routes. The results are the development of three cultural attraction routes: 1) Dvaravati route, the path to learn the traces of archaeological sites from the Dvaravati period with the extension route to Jansen museum in Nakhon Sawan province, 2) the heroes of Bang Rachan route, which is a learning route based on the history of Bang Rachan wih the extension routes to Ang Thong and Chainat provinces and 3) local lifestyle route, which is a way to explore local life and to learn about the culture and identity of local Sing Buri. Each route explores the feasibility of organizing existing resources to be community attractions and distributes income from tourism to the community, including supports for cultural heritage sites managed by the community itself. And findings which will help promote tourism in Sing Buri and benefit the local communities are the improvements in four areas: transportation, restaurants in the tourist attractions, learning options and public relations